2000
DOI: 10.1021/jp9931455
|View full text |Cite
|
Sign up to set email alerts
|

Static and Dynamic Fluorescence of Pyrene as Probes of Site Polarity and Morphology in Ethylene-co-(Vinyl Acetate) (Eva) Films

Abstract: Static and dynamic fluorescence of pyrene has been used to study the polarity of microenvironments of ethylene-co-(vinyl acetate) copolymers of varying compositions. The polarity of these copolymers, defined by the Py-scale, has been compared with low-density polyethylene and poly(vinyl acetate). Linear correlations between vinyl acetate content and either the vibronic ratio, I/III, of the pyrene fluorescence spectra or the fluorescence decay constants, τF, have been obtained. We have also studied the photophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0
14

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 51 publications
1
47
0
14
Order By: Relevance
“…In addition, lower τ in the surface than in bulk should also be expected taking into account that labels at the polymer-air surface may be quenched by oxygen more easily than in bulk. By the other hand, the same result than here reported, larger τ in the surface than in bulk, was observed for pyrene probes deposited on a polymer surface by sublimation of the chromophore 34 or in LB films in which pyrene probes motion was highly restricted so that τ were longer than those in THF solution. 35 This leaves an open question that will be studied in future work.…”
Section: Resultssupporting
confidence: 89%
“…In addition, lower τ in the surface than in bulk should also be expected taking into account that labels at the polymer-air surface may be quenched by oxygen more easily than in bulk. By the other hand, the same result than here reported, larger τ in the surface than in bulk, was observed for pyrene probes deposited on a polymer surface by sublimation of the chromophore 34 or in LB films in which pyrene probes motion was highly restricted so that τ were longer than those in THF solution. 35 This leaves an open question that will be studied in future work.…”
Section: Resultssupporting
confidence: 89%
“…75,76 In the current study, we show that T g values can be obtained in supported polymer films and, for the first time, in free-standing polymer films using a self-referencing fluorescence intensity ratio. Additionally, we provide the first demonstration of the applicability of this approach for determination of T g as a function of confinement in free-standing PS films and show that our data are in approximate agreement with data obtained by Forrest and coworkers.…”
mentioning
confidence: 58%
“…The MApyrene-labeled PiBMA film provides the clearest indication of four peaks in the 370-415 nm wavelength range, which are characteristic of the fluorescence from the excited-state of a single pyrene molecule or pyrenyl chromophore. [75][76][77][80][81][82] In contrast to the fluorescence from the PiBMA film, the second fluorescence peak is virtually absent in the PS films.…”
Section: Fluorescence Measurementsmentioning
confidence: 99%
“…Thus it appears that temperature changes in rigid polymer media affects more strongly the I 1 (S 1 ν=0 → S 0 ν=0 ) vibronic band transition than the I 3 (S 1 ν=0 → S 0 ν=1 ) band and this is probably due to differences in vibronic coupling contributions [23]. Analysis of the excitation spectra monitored at the emission of the first vibronic band of pyrene doped polymer films recorded at various temperatures, indicated that there was no excimer formation associated with these mild experimental conditions [32][33][34][35][36][37][38]. Figure 4d shows a plot of the thermally induced changes in the I 1 /I 3 ratio (py parameter) for the different dry poly(NIPAM-co-NtBA) films.…”
Section: Pyrene Fluorescencementioning
confidence: 99%